Is the international legal order unraveling? - Sloss, David (New York, NY : Oxford University Press, 2022)
Examines how the rules-based international order is threatened by challenges such as climate change, autonomous weapons, and cyber weapons. It discusses how the international order can confront these threats, and proposes future developments of the rules-based international order as a whole.
Also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 3, 2022).
Keywords: International law -- Philosophy; Rule of law -- Philosophy; International relations; World politics; Law; International law